Model Pengembangan Mutu Pendidikan (Tinjauan Konsep Mutu Kaoru Ishikawa) - Roni Harsoyo (Southeast Asian Journal of Islamic Education Management, 2021)
The purpose of writing this article is to examine the concept of improving the quality of Kaoru Ishikawa and its implementation in improving the quality of education. Quality according to Ishikawa is customer satisfaction and quality is not only product quality but also includes people, processes, and every aspect of the organization. The quality improvement effort made by Ishikawa is by implementing a Quality Control system. In this effort, Ishikawa recommends establishing a QC Circle and the use of basic quality tools, one of which is the Cause and Effect Diagram. This Ishikawa quality concept can be implemented in education, including: 1) Improving the Quality of Education Output through Quality Control; and 2) The basis for formulating a strategy to improve the quality of education based on cause and effect. The concept of Ishikawa quality improvement provides motivation for educational institutions to carry out good quality management, one of which is consistency in carrying out quality control through the formation of a QC Circle and the use of quality control tools, one of which is the Cause and Effect Diagram. Thus, educational institutions can improve their quality by knowing the root causes of the problems that occur and determining the appropriate quality improvement strategy.